Gender Peculiarities of Senior Adolescents’ Representations of Successful Relationships with Parents - Pavliuk, Tetyana M. (Psychological Prospects Journal, 2017)
The article represents the results of empirical study of senior adolescents’ gender-specific representations about successful relationships with their parents. The sample contained 120 people, the 9th‑grade-students of Lutsk gymnasiums and secondary schools, 14−15 years old, including 48 boys and 72 girls. The results of empirical study allowed revealing three groups of adolescents by the psychological type of gender identity: masculine, feminine, androgynous. It was found out that each of these groups has its own particular ideas about successful relationships with parents. So, masculine teens associate them primarily with the provision of child autonomy, which is based on mutual trust, confidence in the child abilities, and absence of strict parental control. The need in parents’ emotional acceptance is the lowest as for masculine adolescents among gender groups. Manifestations of parents’ directivity, especially of father, are perceived as the most acute comparing with the feminine and androgynous teenagers. Particular attention is paid to a father’s attitude towards them. The feminine teens see successful relationships with their parents in manifestations of positive attitude towards them; regardless of the initial expectations of the parents and their own concrete successes. Parents’ hostility is most acutely perceived by feminine teens in comparison with the other gender groups. Clear differentiation is discovered in the androgynous adolescents’ representations about successful relationships with parents: from a mother’s side they need unconditional positive perception, emotional understanding, empathy, while from a father’s side they need self-reliance, based on mutual trust and confidence in the child abilities. Androgynous adolescents are characterized by high tolerance to manifestations of parental inconsistency both from father’s and mother’s side. Keywords: parent-child relationships, androgyny, masculinity, femininity, late adolescence.